One Minute Stair Step Test in Predicting VO2 max among Healthy Young Adults - Lisna Anisa Fitriana; Upik Rahmi; Setiawan Setiawan; Lucky Angkawijaya Roring; Hamidie Ronald Daniel Ray; Roman Ardian Goenarjo; Zulkarnain Jaafar; Farida Murtiani (Althea Medical Journal, 2026)
Background: Cardiovascular risk factors such as hypercholesterolemia and hypertension, are increasing among Indonesian young adults despite their apparently healthy status. Valid field methods for assessing VO₂max, a key indicator of cardiorespiratory fitness, are needed for large-scale screening. This study validated the one-minute stair step test (OMSST) against the Bruce treadmill protocol as the reference standard. Methods: This cross-sectional study included 51 healthy males (20.41±0.57 years, BMI 22.52±3.28 kg/m²) in Bandung, Indonesia. VO₂max was measured using the Bruce protocol and estimated using the OMSST (40-cm step, 30 steps/min). Anthropometrics variables, heart rate recovery at 60 seconds (HRR60), and multiple regression variables (age, height, weight, and HRR60) were analyzed using paired t-tests, correlations, and Bland-Altman plots. Results: The mean VO₂max estimated using the OMSST (50.91±3.29 mL/kg/min) closely matched that measured Bruce protocol (49.75±3.61 mL/kg/min; p=0.091), with a small positive bias (1.16 mL/kg/min) and 95% limits of agreement within acceptable bounds. A strong correlation (r=0.85, p<0.001) confirmed validity. HRR60 (91.12±15.10 bpm) significantly predicted VO₂max.Conclusion: OMSST is a valid, simple, low-cost field surrogate for laboratory VO₂max testing in young males, ideal for middle-income settings. Future studies should assess diverse populations and longitudinal reliability.